Organizational changes in the activity of enterprises in the context of urgent crisis management - Kuzmin, O.; Yurynets, O.; Prokopenko, I. (Видавництво Львівської політехніки, 2021)
Eliminating or reducing the negative impact of crisis phenomena on the economic condition of an enterprise and ensuring its further effective development is closely related to the concept of organizational changes. On the one hand, urgent crisis management tools almost always cause such changes. On the other hand, crisis phenomena in the activities of a business entity lead to the need to introduce organizational changes. In this context, it is noted that it is important to diagnose such changes even before their practical implementation begins. This problem is especially relevant when it is necessary to introduce socalled large-scale changes in the context of crisis management. Any mistakes at the beginning most likely will lead to failure to achieve the set goals and to problems in the practical implementation of these changes. Consequently, based on the results of the conducted research, organizational changes in the activities of enterprises in the conditions of crisis management at the beginning are proposed to be diagnosed taking into account four areas that correspond to the PAEI-model of Adizes, well known in the theory and practice. At the same time, it provides for determining the market orientation of organizational changes (proactive nature of organizational changes); the social orientation of organizational changes (integrative nature of organizational changes); the impact of organizational changes on the enterprise administration system (complementary nature of organizational changes); the impact of organizational changes on the operating environment of the enterprise (functional nature of organizational changes). The article offers a method for diagnosing organizational changes in the activities of enterprises in the conditions of crisis management, based on the method of hierarchy analysis (Analytic Hierarchy Process – AHP) and provides for the implementation of such key stages: the formation of an expert group; determining the level of a hierarchical model for diagnosing organizational changes in the conditions of anti-crisis management; studying the essence and characteristics of the proposed organizational changes, so that then diagnose them taking into account the directions of proactive, integrative, functional and complementary nature, using matrices of pairwise comparisons; determining eigenvectors, as well as establishing their normalized values, applying the known geometric mean of the matrix lines; determining the consistency of expert opinions; forming conclusions and recommendations. The possibility of practical use of the proposed method of diagnosing organizational changes in the activities of enterprises in the context of crisis management is confirmed by relevant calculations on the example of several business entities in the Lviv region.
Keywords: crisis management; business; investment; innovation; tools; crisis; enterprise; G32; G33; H12; 338.24.01